(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Through polls of senior high school students, college freshmen, alumnis, and staff at some universities in Vietnam; the article has identified several factors influencing the electronic marketing activities of these universities, primarily focusing on factors affecting the use of electronic marketing tools at these institutions. The results showed that (i) the utility of information provided on the university’s marketing channels is the most significant factor affecting the success of marketing activities in higher education institutions in Vietnam; (ii) the reliability of information shared on the university’s channels also reflects the credibility and reputation of the higher education institution; (iii) improving the quality of education and service delivery is also a factor that can enhance the credibility and brand of universities; (iv) marketing tools need to be user-friendly to ensure that many people can access and disseminate them quickly, conveniently, and easily; (v) the physical facilities of higher education institutions are not currently a significant factor in increasing the effectiveness of their marketing activities.